SERPINA1 Methylation Levels are Associated with Lung Cancer Development in Male Patients with Chronic Obstructive Pulmonary Disease - Zhang LY; Sun XW; Ding YJ; Yan YR; Wang Y; Li CX; Li SQ; Zhang L; Song HJ; Li HP; Li QY (International Journal of COPD, 2022)
Li Yue Zhang,1,2,* Xian Wen Sun,1,2,* Yong Jie Ding,1,2,* Ya Ru Yan,1,2 Yi Wang,1,2 Chuan Xiang Li,1– 3 Shi Qi Li,1,2 Liu Zhang,1,2 He Jie Song,1,2 Hong Peng Li,1,2 Qing Yun Li1,2 1Department of Respiratory and Critical Care Medicine, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Institute of Respiratory Medicine, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Department of Respiratory and Critical Care Medicine, Tongren Hospital Affiliated to Wuhan University, The Third Hospital of Wuhan, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing Yun Li, Department of Respiratory and Critical Care Medicine, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, No. 197, Ruijin Er Road, Shanghai, 200025, People’s Republic of China, Email liqingyun68@hotmail.comPurpose: The mechanism of lung cancer (LC) in male patients with chronic obstructive pulmonary disease (COPD) has not been well understood, and the early diagnosis is currently challenging. The study aimed to explore the association of DNA methylation levels with LC development in male COPD patients.Patients and Methods: A total of 147 male participants were divided into four groups, ie, COPD+LC group, COPD group, LC group, and control (CON) group. The methylation levels of human serine protease inhibitor A1 (SERPINA1) and the serum levels of inflammatory biomarkers were compared among groups. Multivariate logistic regression was performed to explore the correlation of inflammatory biomarkers and gene methylation with lung cancer combining COPD.Results: SERPINA1 methylation levels were significantly higher in the COPD+LC group than that in the COPD group and LC group, respectively (all p